Transformational and Paternalistic Leadership Styles Among Prominent Women Business Leaders - Noor Afza Amran, Marhaiza Ibrahim, Natrah Saad, Zarifah Abdullah, (Opción, 2019)
Today women have become a significant part of the global business environment. The main purpose of this study is to understand the leadership styles of prominent women business leaders and to illustrate the attributes of prominent women business leaders in Malaysia. The transformational and paternalistic leadership styles and the respectis characteristics of prominent women business leaders were highlighted as one of the main findings in this research. The results showed different ways to encourage the spirit of women entrepreneurship to become a successful entrepreneur. A semi structured interview session was utilised with prominent women business leaders and their employees.